Resenhas - Rodrigues, Carla; Nichnig, Claudia Regina; Rosa, Debora Cordeiro; Adrião, Karla Galvão; Oltramari, Leandro Castro; Araújo, Maria Lucília Viveiros; Sell, Mariléia; Zimmermann, Tânia Regina (Revista Estudos Feministas, 2007)
Resenhas